Computer skills for empowering orphans and vulnerable children (OVC) in Malaysia - Madzin, Hizmawati; Ali, Siti Khadijah; Ng, Seng Beng; Mohd Norowi, Noris; Ahmad Supian, Muzaiyanah (Primrose Hall Publishing, 2020)
Orphans and vulnerable children (OVC) can be defined as children who lost their parents due to AIDS. OVC may lose interest in school due to poverty, emotional and parental sickness or death. These reasons may lead OVC to have low self-esteem and lack of computer skills. Therefore, it is significant for the community to provide educational support for OVC. Computer skill can be defined as a life skill in today’s world. However, OVC have limited access to learn computer skills due to hardship in life. University Putra Malaysia (UPM) took up the initiative to transfer knowledge of computer skills program to OVC. This article evaluates the impact of OVC in Malaysia to learn computer skills. Finding shows 50% of the participants responded to have an interest in and high motivation to learn computer skills. It proves that university community can have the ability to provide educational support to OVC.